The etymology, concept and the nature knowability of the sacred numbers in Kazakh and Chinese languages. - Katbayeva, G. K.; Amangeldi, S. D. (Journal of Oriental Studies, 2016)
The main aim of this scientifi c article to introduce the sacred numbers of kazakh and chinese languages. The author reveals the etymology and cognition of numbers.